Promoting Renewable Energy through Auctions : The Case of India - Khana, Ashish (World Bank, Washington, DC, 2014)
This knowledge note singles out auctions as an important mechanism that has been implemented in a growing number of countries in recent decades. It features a case study of auctions designed to promote the generation of electricity from renewable sources in India. The country's national- and state-level experience with auctions of solar energy products both large and small attests to the flexibility and adaptability of auction mechanisms. Under the National Solar Mission, auctions have been implemented with good results in a variety of settings. Lessons include the importance of clear ideas about key goals and objectives, and about areas where sacrifices can be made. Experience in several states has also underlined the importance of regulatory stability. This case study is interesting, because India's National Solar Mission led to concurrent implementations of renewable auction schemes. Both national- and state-level auctions have led to successful projects. The Indian central government's experience with auction implementations can be split into three main segments. Phase 1 auctions concern centralized auctions for procuring utility-scale solar plants. Rooftop auctions concern central government conducted auctions for rooftop solar generation in specific cities. No centralized auctions for large-scale solar generation were conducted in 2012 or 2013, so phase 2 auction were created under a new bidding process. Successive delays that were observed in the implementation of phase 2 auctions had negative results. Investors need to feel secure before they will establish a strong manufacturing or developer base.